Researching Spontaneous Doing: Random Dance as Decolonial Praxis in Dancing Grandmothers - Park, Minu (Performance Matters, 2023)
How are “hunch” and “intuition” passed on, and what kinds of knowledge are they? This essay examines Dancing Grandmothers (2011), a contemporary dance piece by Eun-me Ahn Dance Company, to study the piece’s production and transmission of embodied knowledge. The work’s dramaturgy of imperfection foregrounds makchum (random dance) as an important site of knowledge. The raw aesthetic of makchum revives the connection with the physical unconscious by decolonizing cognitive and embodied knowledge. I borrow from Ben Spatz’s epistemology of embodiment to analyze the “amateur” dance portion of Dancing Grandmothers, a section of the work that goes on stage without a rehearsal, and its invitation for the audience members to respond in embodied listening. Dancing Grandmothers is a form of decolonizing from within, where knowledge shifts mainly through remapping the perceptual rhetoric. It attempts to let the bodies speak for themselves, in equal authority with the dancers who co-create the piece. On top of contributing to a cognitive turn, the joy of dancing central to the performance conveys that animation, vitality, and revival are essential parts of knowledge, generating new energies by stimulating the senses.